Consumer Attitude Toward Online Shopping in Lalitpur Valley - Shrestha, Ranu (Journal of Kathmandu BernHardt College, 2022)
The study focuses on consumer attitudes towards online shopping inside Lalitpur Valley. The study used 150 sample sizes through convenience and random sampling methods. The objectives of the study have to examine the factors affecting on consumer attitudes towards online shopping as well as to identify the effect of comfort, cost and security on dependent variables of consumer attitudes toward online shopping. The conceptual framework has used independent variables i.e., comfort, cost, security and dependent variables consumer attitudes toward online shopping. The finding of the study has expressed that cost has the highest mean among three variables whereas inferential statical tools i.e., correlation regression has expressed that comfort, cost and security have positively correlated with dependent variables.